2018
DOI: 10.1177/0300060517750284
|View full text |Cite
|
Sign up to set email alerts
|

In vitro anti-influenza virus effect of total flavonoid from Trollius ledebouri Reichb

Abstract: ObjectiveTo investigate the in vitro antivirus effect of total flavonoid from Trollius ledebouri Reichb (TFTLR).MethodsMadin-Darby canine kidney (MDCK) and Human epithelial type 2 (HEp-2) cell lines were used to test the antivirus effect of TFTLR on nine virus subtypes: four H1N1, one H3N2, and four other subtypes prevalent in North China. Tamiflu, Ribavirin and Lianhua Qingwen were used as active comparators. Comprehensive molecular pathway analyses of TFTLR-H1N1 and TFTLR-H3N2 relationships were also conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…The use of herbal medicine has been accepted in many countries, including regions with improved healthcare systems [ 60 , 61 ]. Most herbal medicinal herbs are inexpensive and have been shown an anti-influenza activity in long-term practice [ 62 , 63 ]. Herbs are rich in biologically active compounds, including phenols, flavonoids, flavonoids, and flavanols.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of herbal medicine has been accepted in many countries, including regions with improved healthcare systems [ 60 , 61 ]. Most herbal medicinal herbs are inexpensive and have been shown an anti-influenza activity in long-term practice [ 62 , 63 ]. Herbs are rich in biologically active compounds, including phenols, flavonoids, flavonoids, and flavanols.…”
Section: Resultsmentioning
confidence: 99%
“…In the CoMFA model, the q 2 is 0.62 with a standard error of estimate of 0.093 and r 2 is 0.973 on the training set. All these researches show a well predicted effect of the compounds, but they are generally focus on only one or two types of derivatives, such as sialic acid analogs and resveratrol derivatives, and the currently known NAIs also include cyclohexene derivatives, cyclopentane derivatives, benzoic acid derivatives, pyrrolidine derivatives, flavonoid analogs, and caffeic acid derivatives [ [20] , [21] , [22] ]. This will lead to a result that the model is only suitable for these derivatives, and it is difficult to get a good prediction effect once the structure of test compounds are different from the training set for modelling.…”
Section: Introductionmentioning
confidence: 99%
“…89 Tanshinone ⅡA inhibits Tat-induced Transactivation of LTR HIV-1 depending on the AMPK-Nampt pathway so that it can be developed into a new anti-HIV agent, 90 oleanolic acid inhibits HIV-1 replication by inhibiting HIV-1 protease activity in vitro, 91,92 and maslinic acid has potent inhibitory activity against HIV-1 proteases. 93 Ladanein Anti-HCV hepatitis C virus (HCV) activity 83 Sinensetin -Treatment of influenza disease with excessive inflammation 31 -Inhibitors of SARS-CoV-2 Guanine-N7 Methyltransferase (in silico study) 77 Cirsimaritin -Inhibitors of COVID-19 main protease (in silico study) 78 -Anti-influenza virus 95 Phenolic Acid 96,43,97,98 Rhamnazin Anti-HCV hepatitis C virus (HCV) activity 99 Rosmarinic acid -Anti enterovirus 71 (EV71) 29,30 -Potential inhibitor of COVID-19 (in silico study) 32,33,73 -Reduces the mortality of mice infected with the Japanese encephalitis virus (JEV) 34 -Inhibit hepatitis B virus replication 36 Caffeic acid -Anti-herpes simplex virus type 1 54 -Inhibition influenza A virus multiplication in vitro 67…”
Section: Anti-human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%
“…Polyphenols, which mainly include flavonoids and phenolic acids [3], are present, in high abundance, amongst the genus Trollius (including T. chinensis and T. ledebouri), and are responsible for the antiviral, antimicrobial, antioxidant activities associated with these plant species [4,5]. Previous research had demonstrated that specific polyphenols impede cancer cell proliferation [6].…”
Section: Introductionmentioning
confidence: 99%